Near-infrared properties of i-drop galaxies in the Hubble Ultra Deep Field - Stanway, E; McMahon, R; Bunker, A (2005)
We analyse near-infrared Hubble Space Telescope (HST)/Near-Infrared Camera and Multi-Object Spectrometer F110W (J) and F160W (H) band photometry of a sample of 27 i′-drop candidate z ≃ 6 galaxies in the central region of the HST/Advanced Camera for Surveys Ultra Deep Field. The infrared colours of the 20 objects not affected by near neighbours are consistent with a high-redshift interpretation. This suggests that the low-redshift contamination of this i′-drop sample is smaller than that observed at brighter magnitudes, where values of 10-40 per cent have been reported. The J-H colours are consistent with a slope flat in f v(f λ ∝ λ -2), as would be expected for an unreddened starburst. However, there is evidence for a marginally bluer spectral slope (f λ ∝ λ -2.2), which is perhaps indicative of an extremely young starburst (∼10 Myr old) or a top heavy initial mass function and little dust. The low levels of contamination, median photometric redshift of z ∼ 6.0 and blue spectral slope, inferred using the near-infrared data, support the validity of the assumptions in our earlier work in estimating the star formation rates, and that the majority of the i-drop candidates galaxies lie at z ∼ 6. © 2005 RAS.